T cells respond preferentially to antigens that are similar to self H-2. - Bevan, M J (1981)
We have constructed bone marrow irradiation chimeras to investigate the influence of self antigens on the specificity of the T lymphocyte receptor repertoire. Bone marrow cells from (A X B)F1 mice heterozygous for the major histocompatibility genes were allowed to mature into T cells in irradiated parent A or parent B strains. More than 8 weeks after irradiation, when the lymphoid system had regenerated from the F1 stem cells, the degree of T cell reactivity to mutant major histocompatibility antigens, A', was assessed. It was found that T cells that had matured in the irradiated A mice, [F1 leads to A] chimeras, responded better to A' antigen than did T cells from the [F1 leads to B] chimeras. Because the mutant histocompatibility antigen A' is very similar in structure to A, differing only by one or a few residues, this suggests that the T cell repertoire in [F1 leads to parent] chimeras reacts preferentially with foreign antigens that are slight variants of the self antigens expressed on radiation-resistant cells--probably cells in the thymus.